Origin and formation of methane in groundwater of glacial origin from the Cambrian-Vendian aquifer system in Estonia - Raidla, Valle; Pärn, Joonas; Schlömer, Stefan; Aeschbach, Werner; Marandi, Andres (Geochimica et cosmochimica acta, 2019)
Groundwater in the Cambrian-Vendian aquifer system in Estonia is characterised by the most depleted isotopic composition known in Europe (δ18O down to −23‰). The water most likely originates from glacial meltwater recharge from the Fennoscandian Ice Sheet in the Pleistocene. The aquifer system is characterised by relative high methane concentrations (up to 50% of dissolved gases, estimated absolute concentration up to 1600μmol L−1), the origin of which has so far remained unclear. In this paper, we focus on the origin of methane, the factors controlling its spatial distribution and its isotope geochemistry in the aquifer system. The data reveal a large spatial variability in methane concentration, δ13CCH4 and δ2HCH4 values (from −6 to −105‰ and from −220 to −420‰, respectively). We show that local oxidation processes rather than different pathways of methane formation, have affected the initial isotopic composition of methane. Using the least modified δ13CCH4 values (from −85 to −105‰), we conclude that methane most likely originates from the organic material overridden by the Fennoscandian Ice Shield during the Late Weichselian glaciation, that was carried into the aquifer system with infiltrating glacial meltwater. The estimated δ18O values of the water, where the methane was formed, are −17±1.5‰ supporting the inference that the methane was formed during the Middle Weichselian interstadial. The study shows that groundwater of glacial origin in the Cambrian-Vendian aquifer system can serve as an alternative palaeoenvironmental archive to be used for studying the variations in climatic and environmental conditions in Northern Europe during glacial-interglacial cycles of the Pleistocene.
Gesehen am 12.03.2019